Language Use as a Means to Construct Realities: Theme Patterns in Joe Biden’s Speech on the Anniversary of the Capitol Attack - Djimet, Issa (European Scientific Journal, ESJ, 2022)
This research work aims at analyzing Joe Biden’s speech on the Capitol attack anniversary from a systemic functional perspective (Halliday &Matthiessen, 2004) so as to decode the thematic choices made by the President to construct some realities through language use as a message. Actually, the article particularly focuses on the textual metafunction to highlight which meaning is prioritized and why. The quantitative and qualitative analyses of Theme patterns have revealed that topical Themes are dominant, followed by textual and interpersonal ones. The thematization of rioters and mob is aimed at emphasizing the actions, feelings and attitudes that have led to the attack and therefore menaced the American democratic system; whereas the use of Donald Trump, he, the former President in topical position has enabled the author of the speech to clarify the former President’s role or responsibility in this attack. As for Joe Biden, the American people and we, they are at the center of a message that restores democratic values. The speech also has an attudinal connotation expressed through interpersonal Themes, which take the form of warnings against undemocratic practices and behaviors while marked Themes have underlined the gravity of the attack as regards the place and the time at which it took place. The realization of these meanings is achieved through a coherent arrangement of the message in terms of extension and enhancement. Thus, language use can construct any reality.